Petunjuk pelaksanaan teknis evaluasi belajar tahap akhir (EBTA) bagi sekolah/kursus dalam lingkungan Kantor Wilayah Departemen Pendidikan dan Kebudayaan Daerah Khusus Ibukota Jakarta, tahun ajaran 1980/1981 (Kantor Wilayah Departemen P & K DKI Jakarta, 1981)
Regulations of the Jakarta regional office, Dept. of Education, for evaluating scholastic achievements of graduating students in primary and secondary schools in Jakarta; with sample forms.